Human Resource Leadership Management Based on Emotional Intelligence in Educational Institutions - Hosiyatni, Tri Majda; Safitri, Wulan Gita Nur (Proceedings Series on Social Sciences & Humanities, 2025)
Leadership in educational institutions is very important because educational institutions have a main mission, namely to produce the next generation of smart and useful for themselves, society, and the surrounding environment. Educational institutions become a very important place for individuals to seek knowledge and apply the knowledge gained, the function of education management is very important to apply. Management is basically a process of using resources effectively to achieve certain goals or objectives in an organization or institution. This research focuses on how leadership management improves the emotional intelligence of individuals in educational institutions. This research method the author uses the library research method, where in making this journal the main sources are obtained from books, journals, and scientific articles. Therefore, a leader is able to foster a spirit of learning and always motivate the nation's successors/students and understand and realize the abilities that a person has towards what he experiences either through thoughts, words or deeds, not only carrying out obligations or fulfilling obligations but more than that emotional intelligence must be truly realized clearly.